2014
DOI: 10.1155/2014/986453
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Infiltration Masquerading Distant Adenocarcinoma

Abstract: Malignant metastasis to the psoas muscle is rare. We report a case that clinically mimicked psoas abscess that was subsequently proven to be from metastatic disease secondary to adenocarcinoma of the duodenum. A 62-year-old male presented with a seven-month history of right lower quadrant abdominal pain and progressive dysphagia. CT scan of abdomen-pelvis revealed a right psoas infiltration not amenable to surgical drainage. Patient was treated with two courses of oral antibiotics without improvement. Repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Repeated CT scan showed ill-defined low-density area with inflammatory changes involving the right psoas muscle. In this report, a fine needle aspiration biopsy of the right psoas was performed by CT guidance to obtain the histopathologic diagnosis [7]. Singh et al reported a 68-year-old male patient presented with fever, groin pain, leukocytosis and azotemia mimicking pyelonephritis that was subsequently proven to be from a diffuse, large, B-cell lymphoma by fineneedle aspiration cytology and biopsy from the lesions.…”
Section: Discussionmentioning
confidence: 96%
“…Repeated CT scan showed ill-defined low-density area with inflammatory changes involving the right psoas muscle. In this report, a fine needle aspiration biopsy of the right psoas was performed by CT guidance to obtain the histopathologic diagnosis [7]. Singh et al reported a 68-year-old male patient presented with fever, groin pain, leukocytosis and azotemia mimicking pyelonephritis that was subsequently proven to be from a diffuse, large, B-cell lymphoma by fineneedle aspiration cytology and biopsy from the lesions.…”
Section: Discussionmentioning
confidence: 96%
“…The most common metastatic sites of lung cancer are the adrenal glands, liver, bone, and brain—as seen with the renal and liver lesions discovered in our case [ 7 ]. Frequent sites of skeletal muscle metastatic involvement, specifically in lung cancer, include the thigh, iliopsoas, and paraspinous muscles, though lesions in the orbit and pectoral muscles have been described [ 4 , 8 – 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup analysis revealed that masses of pulmonary origin had low central attenuation with rim enhancement as the most common finding on CT [ 13 ]. Correlation with FDG-PET is recommended in all patients with a history of malignancy or a suspicion lesion [ 3 , 8 , 9 , 18 ]. Biopsy of these masses is mandatory for proper diagnosis and further management [ 6 , 9 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those cases found during the staging for a known primary cancer were excluded. We found only a few reported cases [4][5][6][7][8][9][10] ; a summary is shown in Table 1.…”
mentioning
confidence: 99%
“…Among these cases, only the reports by Tonelli et al 10 and Gharaibeh et al 5 indicated “crural neuralgia” and “groin and anterior thigh pain,” respectively, as the initial symptoms of psoas muscle metastasis, disclosing a hidden primary cancer. However, these reports lacked an electrodiagnostic verification of femoral neuropathy.…”
mentioning
confidence: 99%